1.1. Given: (i) \( A=60^{\circ} \) and \( B=30^{\circ} \) (ii) \( A=110^{\circ} \) and \( B=50^{\circ} \) (iii) \( A=225^{\circ} \) and \( B=135^{\circ} \) Use a calculator to evaluate each of the following: (a) \( \cos (A-B) \) (b) \( \cos A-\cos B \) (c) \( \cos A \cos B+\sin A \sin B \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
Let's go through the given pairs of angles one by one and calculate the required values. ### For \( A = 60^{\circ} \) and \( B = 30^{\circ} \): 1. **(a)** \( \cos (A-B) = \cos(60^{\circ} - 30^{\circ}) = \cos(30^{\circ}) = \frac{\sqrt{3}}{2} \) 2. **(b)** \( \cos A - \cos B = \cos(60^{\circ}) - \cos(30^{\circ}) = \frac{1}{2} - \frac{\sqrt{3}}{2} = \frac{1 - \sqrt{3}}{2} \) 3. **(c)** \( \cos A \cos B + \sin A \sin B = \cos(60^{\circ}) \cos(30^{\circ}) + \sin(60^{\circ}) \sin(30^{\circ}) = \left(\frac{1}{2} \cdot \frac{\sqrt{3}}{2}\right) + \left(\frac{\sqrt{3}}{2} \cdot \frac{1}{2}\right) = \frac{\sqrt{3}}{4} + \frac{\sqrt{3}}{4} = \frac{\sqrt{3}}{2} \) ### For \( A = 110^{\circ} \) and \( B = 50^{\circ} \): 1. **(a)** \( \cos (A-B) = \cos(110^{\circ} - 50^{\circ}) = \cos(60^{\circ}) = \frac{1}{2} \) 2. **(b)** \( \cos A - \cos B = \cos(110^{\circ}) - \cos(50^{\circ}) \approx -0.342 - 0.643 = -0.985 \) 3. **(c)** \( \cos A \cos B + \sin A \sin B = \cos(110^{\circ}) \cos(50^{\circ}) + \sin(110^{\circ}) \sin(50^{\circ}) \approx -0.342 \cdot 0.643 + 0.939 \cdot 0.766 \approx -0.220 + 0.719 = 0.499 \) ### For \( A = 225^{\circ} \) and \( B = 135^{\circ} \): 1. **(a)** \( \cos (A-B) = \cos(225^{\circ} - 135^{\circ}) = \cos(90^{\circ}) = 0 \) 2. **(b)** \( \cos A - \cos B = \cos(225^{\circ}) - \cos(135^{\circ}) = -\frac{\sqrt{2}}{2} - (-\frac{\sqrt{2}}{2}) = 0 \) 3. **(c)** \( \cos A \cos B + \sin A \sin B = \cos(225^{\circ}) \cos(135^{\circ}) + \sin(225^{\circ}) \sin(135^{\circ}) = \left(-\frac{\sqrt{2}}{2} \cdot -\frac{\sqrt{2}}{2}\right) + \left(-\frac{\sqrt{2}}{2} \cdot \frac{\sqrt{2}}{2}\right) = \frac{1}{2} - \frac{1}{2} = 0 \) Thus, the calculations yield the following results: 1. For \( (A=60^{\circ}, B=30^{\circ}) \): - \( (a) \ \frac{\sqrt{3}}{2}, \ (b) \ \frac{1 - \sqrt{3}}{2}, \ (c) \ \frac{\sqrt{3}}{2} \) 2. For \( (A=110^{\circ}, B=50^{\circ}) \): - \( (a) \ \frac{1}{2}, \ (b) \ -0.985, \ (c) \ 0.499 \) 3. For \( (A=225^{\circ}, B=135^{\circ}) \): - \( (a) \ 0, \ (b) \ 0, \ (c) \ 0 \)